Metabolic Reprogramming Underlying Brain Metastasis of Breast Cancer - Liu, Baoyi; Zhang, Xin (Frontiers in Molecular Biosciences, 2022)
The development of brain metastasis is a major cause of death in patients with breast cancer, characterized by rapid progression of the disease and poor prognosis, and lack of effective treatment has existed as an unresolved issue clinically. Extensive research has shown that a variety of metabolic changes associated with cellular metastasis exist in primary breast cancer or brain metastases, therefore to elucidate metabolic characteristics at each step of the metastasis cascade will provide important clues to the efficient treatment. In this review, we discuss the changes in metabolic patterns of breast cancer cells at every step of metastasis for exploring the potential therapeutic target based on metabolic reprogramming, and provide new insights on the design and development of drugs for breast cancer brain metastasis.